Management education for the world a vision for business schools serving people and planet - Muff, Katrin; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
50+20 not only raises the sights for those charged with the development of our future leaders, but also provides a clear roadmap for delivering on that ambition. As such, it is an important contribution to a journey of transformation that affects not only the future of business, but the very planet itself. Paul Polman, Unilever, USThe 50+20 initiative is an ambitious effort that highlights the urgent need for radical change in what we teach and how management education is delivered today. In a world that faces so many different and fast-evolving challenges, the initiative is indeed timely and needed. Peter Bakker, World Business Council for Sustainable Development, SwitzerlandWe now finally have a blueprint that can be used as a foundation for a new contract between business schools and society. Changing the way we educate our business leaders for tomorrow will change the world for the better. Rakesh Khurana, Harvard Business School, USFor many years commentators have described what is wrong with business schools characterizing them as the breeding grounds of a culture of greed and self-enrichment in global business at the expense of the rest of society and of nature. Management Education for the World is a response to this critique and a handbook for those seeking to educate and create knowledge for a new breed of business leaders. It presents a vision for the transformation of management education in service of the common good and explains how such a vision can be implemented in practice. The 50+20 vision, as it is also known, was developed through a collaborative initiative between the Globally Responsible Leadership Initiative, the World Business School Council for Sustainable Business and the U.N.-backed Principles of Responsible Management Education and draws on the expertise of sustainability scholars, business and business school leaders and thought leaders from many other walks of life.This book explores the 21st century agenda of management education, identifying three fundamental goals: educating and developing globally responsible leaders, enabling business organizations to serve the common good, and engaging in the transformation of business and the economy. It is a clarion call of service to society for a sector lost between the interests of faculty, business and the schools themselves at the expense of people and planet. It sees business education stepping up to the plate with the ability of holding and creating a space to provide responsible leadership for a sustainable world embodied in the central and unifying element of the 50+20 vision, the collaboratory.Management Education for the World is written for everyone concerned or passionate about the future of management education: consultants, facilitators, entrepreneurs and leaders in organizations of any kind, as well as policymakers and others with an interest in new and transformative thinking in the field. In particular, teachers, researchers, students and administrators will find it an invaluable resource on their journey.
pt. I. The challenge -- pt. II. The vision -- pt. III. The implementation.
Includes bibliographical references and index.
Keywords: Business education; Electronic books